Outcome of Head Injury Patients Undergoing Surgical Management: A Tertiary Level Experience - Shrestha, A; Joshi, R M; Thapa, A; Devkota, U P; Gongal, D N (Kathmandu University Medical Journal, 2012)
Background Head injury is the major cause of death in a neurosurgical patient. Objective To find the outcome, and treatment modality affecting the outcome in patients with head injury. Methods Nine hundred eighty seven patients presenting to National Institute of Neurological and Allied Sciences, Kathmandu, with head injury from September 2009 to October 2010 were included in the study. Patients were categorized according to post resuscitation Glasgow Coma Score. Outcome was assessed at discharge using Glasgow Outcome Score and analyzed for any correlation with modality of treatment and severity of injury. Results Among 987 patients with head injury,152 (15.4%) had severe, 126 (12.8%) had moderate and 709 (71.8%) had mild head injuries. Three hundred twelve (31.6%) patients required definitive and supportive surgical intervention. One hundred eighty two required cranial surgical intervention. Overall mortality was 10% (99), 137 patients (13.9%) had unfavorable outcome and 850 (86.1%) had favorable Glasgow Outcome Score of 4 and 5. Mortality was 53.2%, 9.5% and 0.8% in severe, moderate and mild head injury group respectively. Mortality rate was significantly higher (64.6%) in severe head injury group managed conservatively than those in same group treated with supportive and definite surgical intervention (44.8%) (p=0.016). Conclusion Mortality in head injury patients depend upon severity of injury. Mortality in severe head injury group can be reduced by supportive and definite surgical intervention. DOI: http://dx.doi.org/10.3126/kumj.v9i4.6345 Kathmandu Univ Med J 2011;9(4):283-5